If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4p + -7q) + (5q + -8p) = 0 Remove parenthesis around (4p + -7q) 4p + -7q + (5q + -8p) = 0 Reorder the terms: 4p + -7q + (-8p + 5q) = 0 Remove parenthesis around (-8p + 5q) 4p + -7q + -8p + 5q = 0 Reorder the terms: 4p + -8p + -7q + 5q = 0 Combine like terms: 4p + -8p = -4p -4p + -7q + 5q = 0 Combine like terms: -7q + 5q = -2q -4p + -2q = 0 Solving -4p + -2q = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '2q' to each side of the equation. -4p + -2q + 2q = 0 + 2q Combine like terms: -2q + 2q = 0 -4p + 0 = 0 + 2q -4p = 0 + 2q Remove the zero: -4p = 2q Divide each side by '-4'. p = -0.5q Simplifying p = -0.5q
| 36x-1=-1+4(x+56) | | -80x^2+120x+610=660 | | 5x^4-9x+4=0 | | 9x^2-20=8x | | y=2(-3)-5 | | ln(6x-3)+3=10 | | 5x-27=6y | | 2/x+3-1/2=3 | | 4x/2x^-1/2 | | x=-3y+8 | | 4y^2+16y+2x+10=0 | | 2x+2y=310 | | y=ln(sinx) | | 8x+4y+9x= | | 12x+8=-4 | | 4y^2+16y+2+10=0 | | 3(2x+3)-5(7-4x)-2(5x+4)=-2 | | -5x/4=12 | | y=7/4x-2 | | 225=16x+x^2 | | -2w-22=3(w-4) | | (-5/4)x=12 | | 4x+8-9x=16-19x+14x-8 | | 4d-7=35 | | 6x+3-9=0 | | x+7900=13220 | | y=-4/3(-3)+4 | | sinv=0.26 | | 6m^2-3=9 | | 8m+3n-2m+7n= | | -13=-6x-10 | | x-2/5x-2/5x-5=15 |